Capital deepening and wage differentials: Germany vs. US - Winfried Koeniger; Marco Leonardi (Institute for the Study of Labor (IZA), 2006)
Capital deepening may affect the evolution of the wage differential between skilled and unskilled workers differently in countries with different labor market institutions. If labor market institutions raise the relative wage of unskilled workers in Germany, firms have incentives to invest relatively more into capital equipment complementary to unskilled workers. Instead in the US, where wage-compressing institutions are weaker, firms invest more in high-skilled workers. We provide evidence consistent with this view based on an industry panel for West Germany and the US between the 1970s and 1990s. We show that capital equipment per worker is less positively associated with the wage differential in West Germany than in the US. This descriptive evidence is robust to many alternative measures for capital and skills. Our estimates imply that capital deepening in Germany in the 1980s is associated with a reduction in the wage differential of about 10-20% in most industries. In the US instead, capital deepening is associated with an increase of the wage differential between 5 and 15% in most industries.
Keywords: E22; E24; J31; J64; 330; capital deepening; skill premium; wage floors; institutions; Arbeitsmarkt; Kapitalintensität; Lohnstruktur; Qualifikation; Deutschland; USA